Effect of nano-silica surface-capped by bis[3-(triethoxysilyl)propyl] tetrasulfide on the mechanical properties of styrene-butadiene rubber/butadiene rubber nanocomposites. (December 2018) - Tian, Qingfeng; Tang, Yuan; Ding, Tao; Li, Xiaohong; Zhang, Zhijun
Abstract: Bis[3-(triethoxysilyl)propyl]tetrasulfide (Si69, denoted as TESPT), a commercial silane coupling agent, was loaded onto the surface of nano-silica by in-situ surface-modification method to obtain surface-functionalized nano-silica (Si-S x ). The effect of the as-obtained Si-S x as filler on the mechanical properties of styrene-butadiene rubber/butadiene rubber (SSBR/BR) composites was investigated. Findings indicate that the silanol of TESPT is chemically bonded onto the surface of nano-silica, thereby significantly increasing the curing efficiency of the rubber-matrix nanocomposite and improving their mechanical properties. This is because the in-situ surface-modification of nano-silica by the Si69 silane coupling agent contributes greatly to increasing the miscibility and compatibility of the nano-silica filler with the rubber matrix. Graphical abstract: Highlights: Surface capped nanosilica was efficiently in-situ synthesized with modifier TESPT. Curing parameters were easily adjusted by changing grafted amount of TESPT. A multi-effect nanosilica additive was designed to improve rubber performance.